TREE PLANTING TO ENCOURAGE ECOTOURISM CONCEPT IN KOPENG VILLAGE: PKM PENANAMAN POHON UNTUK MENDORONG KONSEP EKOWISATA DI DESA KOPENG - Avi Budi Setiawan; Karsinah; Wisudani Rachmaningtyas (Yayasan Education and Social Center, 2021)
Kopeng Village is one of the Vocational Villages in the Getasan Subdistrict. The problems faced by Kopeng Village include the reduction of water catchment areas due to the transfer of land functions into settlements. This is because the tourism sector began to develop and encouraged high physical development such as homestays, housing, and supporting infrastructure. Agricultural activities also tend to change the hue of nature. Many trees that are located in the fields must be cut down not to block the sunlight. As a result, rainwater also cannot be absorbed into the ground but flows to the surface. Also, Kopeng is vulnerable to landslides. This is because the village's location is in the highlands, and the amount of critical land scattered. Also, the critical land is not covered with plant vegetation, so it is prone to landslides in the rainy season. Many critical lands are located very close to residential areas and are instead used as agricultural land. This condition is undoubtedly dangerous for the safety of residents. Moreover, Kopeng village becomes one of the tourist villages, so disaster mitigation should always take precedence. A lot of vacant lands are also untapped. Whereas if used, adding coverage of green areas is also beneficial for the community's welfare through the results of the tree. Therefore, the greening movement in Kopeng village needs to be one of the urgent programs to be carried out immediately. So that later indirectly will support the existing role as a vocational village and tourist village. The planted plant is a type of annual perennial, considering the fruit commodity is not so good when planted in the highlands. Other than that, the perennial has a solid rooting system and the ability to instigate oxygen. Some commodities that can be planted include fir, red shoots, Dutch teak, and acacia. The selection of perennials is expected to produce wood in the next few years and supply oxygen to strengthen kopeng village as an ecotourism area